c - 9 (b, 2005)
Articles on 20th century intellectual life and social customs of Bengali (South Asian people) of India .
Includes index.
In Bengali.
Keywords: Bengali (South Asian people) -- Intellectual life -- 20th century; Bengali (South Asian people) -- Social life and customs -- 20th century